Social resilience of Pudak Sari Kelapa shop production business actors through digitalization of MSMEs in Gresik - Jannah, Asmaul; Mutmainnah (Digital Theory, Culture & Society, 2024)
This research is motivated by the threats that MSMEs face in the digital age and must overcome to remain relevant and sustainable. One of the major challenges comes from the large number of similar business competitors as well as the Covid-19 pandemic, which has drastically changed consumer behavior. The purpose of this research is to determine the social resilience of Pudak Sari Kelapa Shop production business actors through the digitization of MSMEs in Sukodono Village, Gresik District, Gresik Regency. This research uses a qualitative research method with a case study approach. Supported by the theory of social resilience as an analytical tool to explain the digitalization of MSMEs by Pudak Sari Kelapa Shop production business actors. The research results show that there are main aspects in the formation of social resilience of business actors, namely stability, adaptation and transformation. Digitization of MSMEs is not only a means of survival, but also a driver of sustainable business transformation. For example, the implementation of accounting transactions through digital computer methods, payment methods through Qris, and then marketing and selling products through social media and marketplaces. As well as shop renovation efforts that are strengthened by individual resilience, namely the ability to manage emergency fund reserves.